Determinant of Vocational High School’s Open Unemployment - Mahroza, Ayu Dian (Efficient: Indonesian Journal of Development Economics, 2021)
This study aimed to determine the effect of gender, school origin status, national exam scores, work experience, residence and English language skills on unemployment in Sleman Regency. The data used in this study were primary data obtained through questionnaire distributed to vocational high school alumni who graduated in 2018 and 2019. The sampling technique used was non-probability sampling, while for the analysis, it used logit regression analysis tools. The results showed that the variables of gender and school origin status had positive and significant effects on unemployment opportunities for vocational high school graduates. The variables of national exam scores, work experience and English language skills had negative and significant effects on the unemployment opportunities of vocational high school graduates. Meanwhile, the length of work experience and distance from residence to city did not have significant effects on the probability of being unemployed for vocational high school graduates. Penelitian ini bertujuan untuk mengetahui pengaruh jenis kelamin, status asal sekolah, nilai ujian nasional, pengalaman kerja, tempat tinggal dan kemampuan bahasa Inggris terhadap pengangguran di Kabupaten Sleman. Data yang digunakan dalam penelitian ini adalah data primer yang diperoleh melalui penyebaran kuesioner kepada alumni SMK lulusan tahun 2018 dan 2019. Teknik pengambilan sampel yang digunakan adalah non-probability sampling, sedangkan untuk analisisnya menggunakan alat analisis regresi logit. Hasil penelitian menunjukkan bahwa variabel jenis kelamin dan status asal sekolah berpengaruh positif dan signifikan terhadap kesempatan kerja lulusan SMK. Variabel nilai ujian nasional, pengalaman kerja dan kemampuan bahasa Inggris berpengaruh negatif dan signifikan terhadap peluang pengangguran lulusan SMK. Sementara itu, lama pengalaman kerja dan jarak tempat tinggal ke kota tidak berpengaruh signifikan terhadap peluang menganggur lulusan SMK.